Clozapine: A special case of an atypical antipsychotic - Elina Marinho (Elsevier, 2024)
The treatment of psychiatric disorders is still an unresolved problem in our society and schizophrenia, the 12th cause of disability in the world, is an important and serious mental disorder. This short review presents a comprehensive overview of the gold standard clozapine developed approximately seven decades ago, which can be considered a milestone in the development of new antipsychotics. It is the first atypical antipsychotic to enter clinical use and is recognized for the treatment of psychiatric illnesses such as schizophrenia and bipolar disorder, as its efficacy is superior to other antipsychotic agents like chlorpromazine. Clozapine is a 5-HT2A and D2 receptor antagonist, as well as a 5-HT1A receptor agonist.